2018
DOI: 10.31676/2073-4948-2018-54-63-66
|View full text |Cite
|
Sign up to set email alerts
|

Genetic resources of black currant in breeding for suitability for mechanized harvesting

Abstract: Резюме. В результате селекционной оценки генетической коллекции смородины чёрной Кокинского опорного пункта ФГБНУ ВСТИСП выделены источники и доноры отдельных признаков пригодности к машинной уборке урожая. Выделены сорта, пригодные к механизированному сбору плодов: Глариоза, Кудесник, Миф, Тамерлан, Чародей, Ben Hopen и др. Ключевые слова: смородина чёрная, генетические источники, сорт, пригодность к механизированной уборке урожая. Summary. As a result of the breeding evaluation of the genetic collection of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…In 2019, as a result of testing the "Joonas-2000" berry harvester (Finland) (Figure 5) on the studied red currant cultivars, it was found that the previously studied limiting and non-limiting signs were fully confirmed in practice. The conclusions made are confirmed in the reports of Dale et al (1994), Gurin (2000), Yakimenko (2001), Barney, Hummer (2005), Danshina (2017), Sazonov (2018), Kanarskiy, Makarychev (2019).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In 2019, as a result of testing the "Joonas-2000" berry harvester (Finland) (Figure 5) on the studied red currant cultivars, it was found that the previously studied limiting and non-limiting signs were fully confirmed in practice. The conclusions made are confirmed in the reports of Dale et al (1994), Gurin (2000), Yakimenko (2001), Barney, Hummer (2005), Danshina (2017), Sazonov (2018), Kanarskiy, Makarychev (2019).…”
Section: Discussionsupporting
confidence: 73%
“…In this experiment, the biological (morphological) features of the structure of the bush (height, width, volume, compactness) were quite stable due to a small range of phenotypic variability, which was confirmed by the relatively low values of the coefficient of variation (CV). The biometric values of the bushes' growth habit are mostly determined by the genetic characteristics of the cultivar and are not subject to changes in the environmental conditions (Sazonov, Danshina 2016;Sazonov 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A little portion of small fruit plantations in huge specialized households is mostly connected with high labor intensity of hand harvesting which takes up to 70 % of all expenses (Sazonov, 2006;Kazakov et al, 2009). Depending on the crop, variety or yield this operation requires 200-300 man work units/ha, which is 3-5 times higher than is necessary for fruit crop harvesting.…”
Section: Resultsmentioning
confidence: 99%
“…An approximate model of the mechanical parameters of black currant berries has been developed to use a mechanized harvester with minimal losses possible with a force of 0.5-1.5 Newton (N) for separation of berries in the cluster and a can rushing force of at least 2.0 N. The physical and mechanical properties of berries can indicate the period of removable maturity, and the commercial qualities of berries will meet the standard criteria [14,22]. However, the most significant disadvantages of black currant cultivars identified during machine harvesting are significant loss of leaves and fragility of branches, causing a reduction in the productive period by about 2-3 years and decreasing the efficiency of harvesters [23][24][25][26][27][28][29][30]. The main parameters such a cultivar should correspond to are distinguished in breeding programs for current technological cultivars.…”
Section: Introductionmentioning
confidence: 99%